Eletrodo impresso de carbono modificado com grafeno e quantum dots de cdte utilizado na determinação do bisfenol A - Felix, Guilherme Cazagrande (Universidade Federal de São Carlos, 2022)
Endocrine disruptors are synthetic or natural compounds that interfere with the normal functioning of the organism. These disruptions affect the alteration of the hormonal system and the metabolic processes that are regulated by the endocrine system, generating as a consequence several diseases such as cancer, hormonal dysfunctions, among others. Bisphenol A is used as a base product in the production of synthetic polymers and it belongs to a part of this class of compounds, and its release and exposure to the environment must be controlled and monitored. Thus, several analytical methods are reported in the literature based on liquid or gas chromatography, with different types of detection. Such methods have high sensitivity, appreciated robustness and great precision and accuracy for the determination of these compounds. However, these methods involve a high laboratory cost, large waste generation, large analysis time and do not allow in-situ analysis. On the other hand, the development of electrochemical sensors presents itself as a fast, sensitive and low-cost alternative for both analysis and production of sensors, when compared to chromatographic methods. In addition, the modification of its sensor surface allows adaptation to specific analytes, which can generate an improvement in the magnitude of the analytical signal. In this sense, a promising material for modifying the surface of sensors are quantum dots. These nanoparticles are smaller than 10 nm in size, have important optoelectronic characteristics due to their quantum confinement and are interesting to be applied in the modification of electrochemical sensors. Thus, in this work, a literature review was carried out on the development of electroanalytical methods for the determination of bisphenol A. A disposable electrochemical sensor manufactured with carbon ink modified with quantum dots of cadmium telluride will also be presented for the determination of BPA in samples of river water. The developed sensor proved to be effective in the determination of BPA, presenting an estimated detection limit of 3.4 nmol L-1 and an estimated recovery when applied to the determination of BPA in river water samples.
Carbon screen printed electrode modified with graphene and CdTe quantum dots for determination of bisphenol A
Keywords: Disruptores enócrinos; Bisfenol A; Quantum dots; Eletrodo impresso de carbono; Eletroanálise; Endocrine disruptors; Bisphenol A; Carbon screen printed electrode; Electroanalysis; CIENCIAS EXATAS E DA TERRA::QUIMICA